PENGARUH IKLAN OBAT BATUK DI TELEVISI TERHADAP PERILAKU SWAMEDIKASI PADA IBU YANG MEMPUNYAI BALITA - Irma Hartati (Jurnal Maternitas Kebidanan, 2022)
Self-medication behavior is strongly influenced by drug-related information from various factors, including education, place of residence, cost, age, occupation, length of illness and one of them is advertising. Television advertising is more effective in visualizing an advertised product. Advertising on a television show is one form of promotion. This study aims to determine the effect of cough medicine advertisements on television on self-medication behavior in mothers who have toddlers. The design in this study is an analytic cross sectional. The population in this study were all mothers who had toddlers in Seunumbok Lapang Village, Peureulak Timur District, East Aceh Regency. The number of samples was 69 respondents using the Proportional Stratified Random Sampling technique. Data collection was done by interview and data analysis was done by univariate method. The results of the study on 69 respondents, the majority knew about cough medicine advertisements on television as many as 41 respondents (59.4%), the majority did not do self-medication as many as 36 respondents (52.2%). There is a relationship between cough medicine advertisements on television and self-medication behavior in mothers who have toddlers with a p-value of 0.000 (p <0.05). The conclusion of this study was that the majority of 69 respondents knew about cough medicine advertisements on television as many as 41 respondents (59.4%), the majority did not self- medicate as many as 36 respondents (52.2%). There is a relationship between cough medicine advertisements on television and self-medication behavior in mothers who have toddlers with a p-value of 0.000 (p <0.05). It is recommended to Saint Cut Nyak Dhien University students to be able to provide knowledge to the public about the use of cough medicine so that there are no mistakes in giving cough medicine to children. Adding references regarding self-medication behavior for further researchers so that they can conduct research with different analyzes.